Protein Nanopore Membranes Prepared by a Simple Langmuir–Schaefer Approach. Issue 46 (12th October 2021) - Schwieters, Magnus S.; Mathieu‐Gaedke, Maria; Westphal, Michael; Dalpke, Raphael; Dirksen, Maxim; Qi, Daizong; Grull, Marco; Bick, Thomas; Taßler, Stephanie; Sauer, Daniel F.; Bonn, Mischa; Wendler, Petra; et al.
Abstract: Filtration through membranes with nanopores is typically associated with high transmembrane pressures and high energy consumption. This problem can be addressed by reducing the respective membrane thickness. Here, a simple procedure is described to prepare ultrathin membranes based on protein nanopores, which exhibit excellent water permeance, two orders of magnitude superior to comparable, industrially applied membranes. Furthermore, incorporation of either closed or open protein nanopores allows tailoring the membrane's ion permeability. To form such membranes, the transmembrane protein ferric hydroxamate uptake protein component A (FhuA) or its open‐pore variant are assembled at the air–water interface of a Langmuir trough, compressed to a dense film, crosslinked by glutaraldehyde, and transferred to various support materials. This approach allows to prepare monolayer or multilayer membranes with a very high density of protein nanopores. Freestanding membranes covering holes up to 5 μm in diameter are visualized by atomic force microscopy (AFM), helium ion microscopy, and transmission electron microscopy. AFM PeakForce quantitative nanomechanical property mapping (PeakForce QNM) demonstrates remarkable mechanical stability and elastic properties of freestanding monolayer membranes with a thickness of only 5 nm. The new protein membrane can pave the way to energy‐efficient nanofiltration. Abstract : Introducing a facile method, protein nanopores are used to prepare an ultrathin yet stable nanofiltration membrane. Advanced microscopic techniques enable visualization of molecular monolayer membranes covering microporous supports. Membranes made from open protein pores show higher ion permeability over those made from almost closed pores. Furthermore, such protein membranes have outstanding water permeance higher than conventional nanofiltration membranes.